Study & education [sound recording] - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (Los Angeles, California Golden Era Productions, 2009)
Presents a lecture delivered by L. Ron Hubbard, concerning the principles of Scientology.
Digital recording.
An L. Ron Hubbard Classic Lecture.
A lecture given on the 13th of August 1964 with transcripts and glossary and a guide with related issues.
Lectured by L. Ron Hubbard.
Recorded with Clear sound, State of the Art Sound Technology®.
Keywords: Scientology; Audiobooks